Evaluation Of Parking Facilities For Delivery Vehicle/Pick-Up At The Ferry Port Of Kalabahi, Alor District, East Nusa Tenggara Province - A. Agus Tjahjono; Yeti Komalasari; Maulana Akbar (Politeknik Transportasi Sungai Danau dan Penyeberangan Palembang, 2019)
The Ferry Port of Kalabahi, Alor District managed by the Services Unit of Transportation Center Business Port Region XIII of East Nusa Tenggara Province. But the implementation is felt not maximized due to parking facilities for delivery vehicle/pick-up inadequate. At the time of crowded conditions often their vehicles to park outside the port. Frequent shuttle delivery vehicle/pick-up parked irregularly due to the lack of parking patterns created. Based on the existing problems, it needs closer analysis of the condition of the parking facility for delivery vehicle/pick-up at the Ferry Port of Kalabahi. The methods used in this research is quantitative research and to analyse the problems based on appendix II Transportation Minister Decree No. 52 of 2004 on the Implementation of Ferry Port and the Director General of Land No. 272 /Hk.105/DrJD/96 About Technical Implementation Guidelines parking facilities. An analysis it is necessary to increase the area for parking facility for delivery vehicle/pick-up and the proposed pattern of service in the port parking lot so more regularly.